2012
DOI: 10.1523/jneurosci.2531-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Channels Regulate Cortical Excitability in Humans

Abstract: Studies in rodents show that transient receptor potential vanilloid 1 (TRPV1) channels regulate glutamate release at central and peripheral synapses. In humans, a number of nonsynonymous single-nucleotide polymorphisms (SNPs) have been described in the TRPV1 gene, and some of them significantly alter the functionality of the channel. To address the possible role of TRPV1 channels in the regulation of synaptic transmission in humans, we studied how TRPV1 genetic polymorphisms affect cortical excitability measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 63 publications
0
59
0
Order By: Relevance
“…TRPV 1 R channels are also expressed in the brain beyond the central endings of the sensory pathways, and are believed to participate in the fine-tuning of several types of synapses (Mezey et al, 2000;Roberts et al, 2004;Grueter et al, 2010;Matta and Ahern, 2011;Mori et al, 2012). Apart from the (anti)nociceptive pathways, functional experiments pointed out presynaptic location for the TRPV 1 R in the forebrain (see Table 1 as well as Matta and Ahern, 2011), while other studies also found it post-synaptically (Tóth et al, 2005;Cristino et al, 2006;Marsch et al, 2007;Li et al, 2008;Maccarrone et al, 2008;Mulder et al, 2011;Grueter et al, 2010;Zschenderlein et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…TRPV 1 R channels are also expressed in the brain beyond the central endings of the sensory pathways, and are believed to participate in the fine-tuning of several types of synapses (Mezey et al, 2000;Roberts et al, 2004;Grueter et al, 2010;Matta and Ahern, 2011;Mori et al, 2012). Apart from the (anti)nociceptive pathways, functional experiments pointed out presynaptic location for the TRPV 1 R in the forebrain (see Table 1 as well as Matta and Ahern, 2011), while other studies also found it post-synaptically (Tóth et al, 2005;Cristino et al, 2006;Marsch et al, 2007;Li et al, 2008;Maccarrone et al, 2008;Mulder et al, 2011;Grueter et al, 2010;Zschenderlein et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report suggests that TRPV1 regulates cortical excitability [54]. This study describes a SNP allele in the TRPV1 channel which is associated with enhanced synaptic transmission in the cerebral cortex.…”
Section: Trp Channels and Migraine Triggersmentioning
confidence: 81%
“…Currently, TRPV1 is thought to be more widely distributed than originally thought and it has been detected in periaqueductal grey, hypothalamus, thalamus, amygdala, cortex, olfactory bulb, trigeminal nucleus caudalis and a number of other regions of the brain in humans, rats and mice [33,34,47,52,53] but see [49]. Several reports have also suggested that TRPV1 is functional in the CNS in several areas including cerebral cortex [54], dentate gyrus [55], and hippocampus [56,57].…”
Section: Trpv1 Localizationmentioning
confidence: 99%
“…28 Additionally, Mori and colleagues have shown that TRPV1 plays a role in cortical excitability by regulating glutamatergic synaptic transmission. 29 In a recent study, Eslamizade et al, 2015 have suggested that Ab could influence excitability of these neurons through modification of the activity of TRPV1. 30 They conclude that dysregulation of PIP2 metabolism by Ab could be partly responsible for neuronal death through changes in TRPV1 function.…”
Section: Trpv Subfamilymentioning
confidence: 99%
“…TRPV4 is a channel activated by temperatures that range from [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] C, by changes in osmotic pressure and by molecules of a lipid nature which are downstream of the activity of PLC, 39 among others. In this case, binding of PIP2 to the N-terminus of TRPV4 was shown to be important for activation of the channel by heat and hypotonic stimuli.…”
mentioning
confidence: 99%